Pharmacodynamic characteristics of lixisenatide once daily versus liraglutide once daily in patients with type 2 diabetes insufficiently controlled on metformin. Issue 7 (25th February 2013) - Kapitza, C.; Forst, T.; Coester, H.‐V.; Poitiers, F.; Ruus, P.; Hincelin‐Méry, A.
ABSTRACT Aim Assess the pharmacodynamics of lixisenatide once daily (QD) versus liraglutide QD in type 2 diabetes insufficiently controlled on metformin. Methods In this 28‐day, randomized, open‐label, parallel‐group, multicentre study (NCT01175473), patients (mean HbA1c 7.3%) received subcutaneous lixisenatide QD (10 µg weeks 1–2, then 20 µg; n = 77) or liraglutide QD (0.6 mg week 1, 1.2 mg week 2, then 1.8 mg; n = 71) 30 min before breakfast. Primary endpoint was change in postprandial plasma glucose (PPG) exposure from baseline to day 28 during a breakfast test meal. Results Lixisenatide reduced PPG significantly more than liraglutide [mean change in AUC0:30–4:30h: −12.6 vs. −4.0 h·mmol/L, respectively; p < 0.0001 (0:30 h = start of meal)]. Change in maximum PPG excursion was −3.9 mmol/l vs. −1.4 mmol/l, respectively (p < 0.0001). More lixisenatide‐treated patients achieved 2‐h PPG <7.8 mmol/l (69% vs. 29%). Changes in fasting plasma glucose were greater with liraglutide (−0.3 vs. −1.3 mmol/l, p < 0.0001). Lixisenatide provided greater decreases in postprandial glucagon (p < 0.05), insulin (p < 0.0001) and C‐peptide (p < 0.0001). Mean HbA1c decreased in both treatment groups (from 7.2% to 6.9% with lixisenatide vs. 7.4% to 6.9% with liraglutide) as did body weight (−1.6 kg vs. −2.4 kg, respectively). Overall incidence of adverse events was lower with lixisenatide (55%) versus liraglutide (65%), with no serious events or hypoglycaemia reported. Conclusions Once daily prebreakfast lixisenatide provided a significantly greater reduction in PPG (AUC) during a morning test meal versus prebreakfast liraglutide. Lixisenatide provided significant decreases in postprandial insulin, C‐peptide (vs. an increase with liraglutide) and glucagon, and better gastrointestinal tolerability than liraglutide.